Hennebique Moves North: The First Applications of Reinforced Concrete in Iceland (1907–10) - NANNINI SOFIA (Politecnico di Torino, 2021)
This essay retraces the early uses of reinforced concrete construction in Iceland in the first decade of the twentieth century. Technical knowledge on reinforced concrete structures reached Iceland much later than other European countries and it was deeply connected to the expertise acquired by the first generation of Icelandic engineers at the Polytechnic School of Copenhagen. This study investigates the adoption of the Hennebique patent by Danish and Icelandic professionals, with a case study of the Danish building firm Christiani & Nielsen. The Icelandic buildings where reinforced concrete was first used were not mere technical accomplishments but major cornerstones in the process towards the political and material independence of the country.